ІV ботанічні читання пам’яті Й.К. Пачоського (Херсон, Україна, 22 – 24.09.2004 р.) (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
ІV ботанічні читання пам’яті Й.К. Пачоського (Херсон, Україна, 22 – 24.09.2004 р.)